Hakikat Dasar Belajar dan Pembelajaran di Sekolah - Dani Nasution, Ananda Bunga Mutiara; Hamdani, Hilmy; Hamid, Asep Lukman (Addabani: Interdisciplinary Journal of Islamic Education, 2025)
This article discusses the nature of learning and instruction as the foundation of education. Research shows that learning is a complex process involving behavior, knowledge, attitudes, skills, and values ​​that change through experience and social interaction. This article aims to understand the differences between learning and instruction and their educational interrelationships. Instruction is a systematic process designed to support learning activities, in which the teacher acts as a facilitator and motivator. The method used is a literature review that analyzes various learning theories, such as behaviorist, cognitive, constructivist, and humanistic, which assist in the design of effective instruction. The research findings emphasize the importance of basic principles in learning, such as individuality, motivation, material relevance, student engagement, and formative evaluation. This article also highlights the importance of a supportive learning environment, effective communication between teachers and students, and innovative learning strategies. Recommendations include training for educators to create an optimal environment for students.